The Role of Adjuvant Chemotherapy in Surgical Stages I-II Serous and Clear Cell Carcinomas and Carcinosarcoma of the Endometrium: A Collaborative Study. Issue 2 (1st January 2011) - Vandenput, Ingrid; Trovik, Jone; Vergote, Ignace; Moerman, Philippe; Leunen, Karin; Berteloot, Patrick; Neven, Patrick; Salvesen, Helga; Amant, Frédéric
Abstract : Objective: To assess the impact of adjuvant chemotherapy in early surgically staged type II endometrial cancer (serous [S], clear cell carcinoma [CC]) and carcinosarcomas (CS) on recurrence and survival. Materials and Methods: Patients diagnosed with stages I-II S-CC and CS after comprehensive surgical staging were retrospectively collected. Surgical staging was defined as pelvic lymphadenectomy of more than 11 nodes harvested and exploration of the upper abdomen, with our without omentectomy. Groups with (group A) and without (group B) platinum-based chemotherapy were compared. Results: We identified 69 patients with a mean age of 66 years (range, 48-88 years). Both groups showed similar baseline characteristics. Group A consisted of 34 patients (23 S-CC, 11 CS) with 10 (29%) recurrences outside the pelvis (7 S-CC, 3 CS). Group B included 35 patients (28 S-CC, 7 CS) of which 10 (29%) developed recurrence outside the pelvis (7 S-CC, 3 CS). The median recurrence-free survival was 22 months (range, 13-51 months) for group A versus 10 months (range, 1-59 months) for group B ( P = 0.437). Five patients (15%) of group A and 9 (26%) of group B died of disease after a median follow-up of 29 months (range, 20-59 months) and 17 months (range, 4-64 months), respectively ( P = 0.168). Conclusion: Recurrences in early-stage type II endometrial cancer and carcinosarcomas occur irrespective of adjuvant chemotherapy, but recurrence-free survival is prolonged when adjuvant chemotherapy is administered. Only prospective randomized intergroup trials can address the benefit of adjuvant chemotherapy in early-stage high-risk endometrial cancer.